Trapped air metamaterial concept for ultrasonic sub-wavelength imaging in water - Laureti, Stefano (Sci Rep, 2020)
Acoustic metamaterials constructed from conventional base materials can exhibit exotic phenomena not commonly found in nature, achieved by combining geometrical and resonance effects. However, the use of polymer-based metamaterials that could operate in water is difficult, due to the low acoustic impedance mismatch between water and polymers. Here we introduce the concept of “trapped air” metamaterial, fabricated via vat photopolymerization, which makes ultrasonic sub-wavelength imaging in water using polymeric metamaterials highly effective. This concept is demonstrated for a holey-structured acoustic metamaterial in water at 200–300 kHz, via both finite element modelling and experimental measurements, but it can be extended to other types of metamaterials. The new approach, which outperforms the usual designs of these structures, indicates a way forward for exploiting additive-manufacturing for realising polymer-based acoustic metamaterials in water at ultrasonic frequencies.